Secondary amine pendent β-peptide polymers realizing antimicrobial surfaces to prevent bacterial infection of implants. (December 2022) - Zhang, Wenjing; Qian, Yuxin; Lu, Ziyi; Deng, Shuai; Xiao, Ximian; Shao, Ning; Xie, Jiayang; Zou, Jingcheng; Ding, Yiru; Chen, Minzhang; Wei, Ting; Yu, Qian; et al.
Highlights: The antibacterial surfaces are prepared using host defense peptide-mimicking β-peptide polymers bearing either primary, secondary or tertiary amine groups. The surface modified with cationic-amphiphilic copolymer P3 containing secondary amino groups is found to have high antibacterial activity and low cytotoxicity. Potent antibacterial activity against drug-resistant bacteria in vitro and in vivo of β-peptide polymer-modified surfaces makes it a favorable candidate for medical implants. Abstract: Antimicrobial coatings covalently grafted on the implant surfaces are considered to be one of the powerful weapons to prevent implant-associated infections. β-Peptide polymers and host defense peptide mimicking polymers are considered promising candidates to fight against drug-resistant bacteria. Here, we compared the antimicrobial activity of Au surface modified by these β-peptide polymers containing primary, secondary, and tertiary amino groups in the side chains. Copolymer P3 containing secondary amino groups was found to have high antibacterial activity. P3-modified thermoplastic polyurethane (TPU) can serve as a promising antimicrobial material for practical application, because of its effective prevention of TPU-related infection and the promotion of host cell growth in the subcutaneous implant infection model. Graphical abstract: Image, graphical abstract